2011
DOI: 10.1016/j.arr.2009.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Age-related defects in the cytoskeleton signaling pathways of CD4 T cells

Abstract: SummaryIt has been postulated that the cytoskeleton controls many aspects of T cell function, including activation, proliferation and apoptosis. Recent advances in our understanding of F-actin polymerization and the Ezrin-Radixin-Moesin (ERM) family of cytoskeleton signal proteins have provided new insights into immunological synapse formation during T cell activation. During aging there is a significant decline of T cell function largely attributable to declines in activation of CD4 T cells and defects in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 151 publications
1
27
0
Order By: Relevance
“…As previously discussed, class switch recombination is impaired in aging murine and human B cells due to decreased expression of enzymes such as AID (53,84). Aberrant T cell signaling has also been associated with aging (48,85), and the list of dysregulated genes continues to grow, as indicated by several recent reports (86)(87)(88), two of which focused on altered expression of dual specific phosphatases (DUSPs). DUSPs deactivate target kinases, including those in the MAPK pathway whose activity is critical for T cell activation, differentiation, and cytokine production.…”
Section: Intracellular Changes In Developing and Mature Lymphocytesmentioning
confidence: 87%
“…As previously discussed, class switch recombination is impaired in aging murine and human B cells due to decreased expression of enzymes such as AID (53,84). Aberrant T cell signaling has also been associated with aging (48,85), and the list of dysregulated genes continues to grow, as indicated by several recent reports (86)(87)(88), two of which focused on altered expression of dual specific phosphatases (DUSPs). DUSPs deactivate target kinases, including those in the MAPK pathway whose activity is critical for T cell activation, differentiation, and cytokine production.…”
Section: Intracellular Changes In Developing and Mature Lymphocytesmentioning
confidence: 87%
“…However, the functional consequences of elevated TORC1 and TORC2 activity and their roles in aging remain unknown (52), with the exception of the association with cancer (53). We have previously shown that CD4 T lymphocytes exhibit alterations in the cytoskeleton, in TCR signaling, and in immune synapse formation that are associated with decreased pERM expression (29) and defects in CD28 signaling (32). Other investigators have reported declines in BIM expression (33).…”
Section: Discussionmentioning
confidence: 99%
“…These alterations include cytoskeletal changes and declines in TCR dependent activation (2529), increased cell size (27), altered RhoA and Rac activity (30), decreased pERM (558) expression (30), and decreased proliferation in vivo (31). We recently demonstrated that some of these defects are the result of alterations in TCR/CD28 signaling (32).…”
Section: Introductionmentioning
confidence: 99%
“…It is unclear whether these changes in cytokine production are associated with L-deprenyl-induced alterations in the populations of T-helper, T-cytotoxic, and T-regulatory lymphocytes but the improvement in cytokine production may have been due to the release of NE by the newly established NA nerve fibers in the spleen as it is an important signal molecule for T cell functions in spleen and lymph nodes [22]. Age-related lymphoproliferative responses in the spleens of female rats were not altered by L-deprenyl treatment indicating that it is unable to reverse the age-associated decline in immunological synapse formation due to impaired cytoskeletal signaling pathways and also, the expression of costimulatory molecule, CD28, on T cells [23, 24]. These impaired signaling pathways and down-regulated expression of major costimulatory molecules such as CD28 in T cells may have been responsible for similar lack of effect of L-deprenyl treatment on T cell proliferation in the spleens of young and old male rats and tumor-bearing female rats [2, 1113].…”
Section: Discussionmentioning
confidence: 99%